(untitled) (Journal of human and social sciences, 2025)
The study aimed to examine the relationship between the conceptual framework of the appropriate value of financial information and capital markets. Design/Methodology/Approach: The researcher conducted an applied study on companies listed on the Egyptian Stock Exchange (EGX100). The study sample was selected from the most active companies in the Egyptian Stock Exchange (30) companies in 2021, through which the researcher aims to identify the problem, then set goals related to addressing this problem, then develop specific hypotheses that cover all aspects of that problem, and test these hypotheses in a scientific way through statistical methods, through which data are identified, measured and analyzed, in order to reach objective results that can achieve the objectives of the study, and the researcher relied on the Excel program to prepare data and use (SPSS) to perform a statistical analysis of the applied study data. The results of the study and the statistics show that the applied study and its conclusions are consistent with the theoretical study that indicates the impact of company size, financial performance, and accounting profits on the market value of shares in the Egyptian stock market. Accordingly, based on the results mentioned above, we accept the alternative hypothesis for all three hypotheses that there is a statistically significant relationship for the independent variables (company size, financial performance, and accounting profits) and the market value of the share, and we reject the null hypothesis for all three hypotheses that there is no significant relationship Statistical for the independent variables (company size, financial performance, and accounting profits) and the market value of the